Electrochemical and X-ray Photoelectron Spectroscopy Characterization of Alkanethiols Adsorbed on Palladium Surfaces - Corthey, Gastón (2009)
The self-assembly of alkanethiolate monolayers on palladium substrates and their stability in aqueous solutions have been studied by electrochemical techniques and X-ray photoelectron spectroscopy (XPS). Alkanethiols adsorb on Pd from ethanolic solutions forming a complex interface which consists of thiolates onto a diluted palladium sulfide interphase, with surface coverages θSulfide ≈ 0.4 and θthiolate ≈ 0.30, respectively. These complex adlayers exhibit hydrocarbon chain-length dependent barrier properties like those formed on Au and Ag substrates. For short chain alkanethiols, thiolates are more stable against reductive desorption than selfassembled monolayers (SAMs) on Au, Ag, and Ni. The increased stability of the organic species seems to be related to the presence of the diluted sulfide layer that also explains the chain length independence of the stability potential range. The stability of these monolayers in aqueous solutions indicates that Pd is a suitable platform for thiolate-based devices such as sensors and biosensors. These results also suggest that electrochemical cleaning should be a simple way to prepare metallic nanoparticles from thiol-capped Pd nanoparticles adsorbed on conducting substrates.